Protocol to study in vivo organ-specific migration of apoptotic splenocytes in mice with tumor and immune checkpoint inhibitor-induced colitis - Lukas M. Braun; Robert Zeiser (STAR Protocols)
Summary: Extracorporeal photopheresis (ECP) reduces immune checkpoint inhibitor (ICI)-induced colitis without affecting anti-tumor immunity. Here, we provide a protocol to trace ECP-treated cells in vivo after transfer into tumor-bearing mice with ICI-induced colitis. We detail tumor and colitis induction, ICI therapy, and the labeling of ECP-treated splenocytes to trace their migration into target organs. Fluorescence imaging and tissue digestion enable the analysis of phagocytic uptake and the analysis of tolerogenic polarization of phagocytes based on congenic markers of donor and recipient mice.For complete details on the use and execution of this protocol, please refer to Braun et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.